N, P and K storage efficiency on degraded peat soil through ameliorant application - E Maftu'ah; A Ma'as; B H Purwanto (Journal of Degraded and Mining Lands Management, 2014)
The availability of nutrients, especially N, P, K in the degraded peat are very low. The high organic acids can decrease the soil pH, its causes the negatively charged nutrients such as nitrate and phosphate are also very low. Ameliorant contributes some cations both monovalent and polivalent which acts as a bridge cations, thus increasing the availability of nutrients, especially nitrogen and phosphate. The objective of research was to determine the storage efficiency of N, P, K on application of some ameliorants on degraded peat land. The experiment was conducted at the laboratory of ISARI, Banjarbaru. Peat soil collected from the degraded peat land at Kalampangan, Central Kalimantan. The treatments were 8 ameliorant formula and two control treatments (+NPK and -NPK). The treatments were arranged in CRD, with 3 replications, And using soil coloum (lysimeter). The leaching was conducted every once a week, with 1.25 liter of aquades and the volume of leachate would be recorded. N, P, K concentration in leachate were analyzed periodically at 1, 2, 4, 6, and 8 weeks after incubation. The results showed that the concentrations of N and K on each observation time were relatively same, but P increased significantly at 4 weeks after incubation. The highest concentrations of N, P, and K in leachate were ameliorant from 100% of chicken manure. The storage efficiency of N, P and K varied depending on the type of ameliorant. Ameliorant that improved storage efficiency of N and K was ameliorant which consist of 80% agricultural weed + 20% dolomite, whereas for P efficiency storage was on ameliorant which consist of 80% Chinese water chestnut (Eleocharis dulcis) + 20% dolomite.